Activation of adenosine A2A receptors in the olfactory tubercle promotes sleep in rodents. (15th May 2020) - Li, Rui; Wang, Yi-Qun; Liu, Wen-Ying; Zhang, Meng-Qi; Li, Lei; Cherasse, Yoan; Schiffmann, Serge N.; de Kerchove d'Exaerde, Alban; Lazarus, Michael; Qu, Wei-Min; Huang, Zhi-Li
Abstract: The olfactory tubercle (OT), an important nucleus in processing sensory information, has been reported to change cortical activity under odor. However, little is known about the physiological role and mechanism of the OT in sleep-wake regulation. The OT expresses abundant adenosine A2A receptors (A2A Rs), which are important in sleep regulation. Therefore, we hypothesized that the OT regulates sleep via A2A Rs. This study examined sleep-wake profiles through electroencephalography and electromyography recordings with pharmacological and chemogenetic manipulations in freely moving rodents. Compared with their controls, activation of OT A2A Rs pharmacologically and OT A2A R neurons via chemogenetics increased non-rapid eye movement sleep for 5 and 3 h, respectively, while blockade of A2A Rs decreased non-rapid eye movement sleep. Tracing and electrophysiological studies showed OT A2A R neurons projected to the ventral pallidum and lateral hypothalamus, forming inhibitory innervations. Together, these findings indicate that A2A Rs in the OT play an important role in sleep regulation. Highlights: Activation of OT A2A Rs increased NREM sleep. Blockade of OT A2A Rs increased sleep latency. Chemogenetic activation of OT A2A R neurons increased NREM sleep. Connections between OT A2A R neurons and neurons in the VP and LH were inhibitory. The study concluded that the OT promotes sleep through A2A Rs and A2AR neurons.